Ethical principles for infodemiology and infoveillance studies concerning infodemic management on social media - Lotto, Matheus; Hanjahanja-Phiri, Thokozani; Padalko, Halyna; Oetomo, Arlene; Butt, Zahid Ahmad; Boger, Jennifer; Millar, Jason; Cruvinel, Thiago; Morita, Plinio P. (Frontiers in Public Health, 2023)
Big data originating from user interactions on social media play an essential role in infodemiology and infoveillance outcomes, supporting the planning and implementation of public health actions. Notably, the extrapolation of these data requires an awareness of different ethical elements. Previous studies have investigated and discussed the adoption of conventional ethical approaches in the contemporary public health digital surveillance space. However, there is a lack of specific ethical guidelines to orient infodemiology and infoveillance studies concerning infodemic on social media, making it challenging to design digital strategies to combat this phenomenon. Hence, it is necessary to explore if traditional ethical pillars can support digital purposes or whether new ones must be proposed since we are confronted with a complex online misinformation scenario. Therefore, this perspective provides an overview of the current scenario of ethics-related issues of infodemiology and infoveillance on social media for infodemics studies.